Predictors of paroxysmal thyrotoxic atrial fibrillation - L. N. Berestennikova; G. A. Chumakova (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To identify the predictors of paroxysmal thyrotoxic atrial fibrillation (AF). Material and methods. The study included 68 patients with AF and thyrotoxicosis. All participants were divided into two groups: Group I (n=51) included patients with paroxysmal AF (mean age 54±8,7 years; 41% men); Group II (n=17) included patients with persistent AF (mean age 50±11 years; 53% men). To identify independent predictors of paroxysmal thyrotoxic AF, logistic regression methods were used. Results. The independent predictors of paroxysmal thyrotoxic AF included free thyroxin level and thyrotoxicosis duration under one year. Conclusion. Compared to persistent AF, paroxysmal AF is an earlier form of cardiac pathology in patients with less severe thyrotoxicosis.